Cohesive slope failure analysis using methods combining smoothed particle hydrodynamics and response surface function. Issue 3 (5th December 2019) - Li, Liang; Chu, Xuesong; Yu, Guangming
Abstract : Purpose: The paper aims to construct a method to simulate the relationship between the parameters of soil properties and the area of sliding mass of the true slip surface of a landslide. Design/methodology/approach: The smoothed particle hydrodynamics (SPH) algorithm is used to calibrate a response surface function which is adopted to quantify the area of sliding mass of the true slip surface for each failure sample in Monte Carlo simulation. The proposed method is illustrated through a homogeneous and a heterogeneous cohesive soil slope. Findings: The comparison of the results between the proposed method and the traditional method using the slip surface with minimum factor of safety (FSmin ) to quantify the failure consequence has shown that the landslide risk tends to be attributed to a variety of risk sources, and that the use of a slip surface with FSmin to quantify the consequence of a landslide underestimates the landslide risk value. The difference of the risk value between the proposed method and the traditional method increases dramatically as the uncertainty of soil properties becomes significant. Practical implications: A geotechnical engineer could use the proposed method to perform slope failure analysis. Originality/value: The failure consequence of a landslide can be rationally predicted using the proposed method.